MODEL PEMBERDAYAAN-PARTISIPATIF MASYARAKAT MELALUI KELOMPOK TANI - Hayat, Sahidin; Saifudin, M; Jauhari, Tontowi (Fakultas Pertanian, Universitas Janabadra, 2024)
Empowerment is an effort to improve the welfare of disadvantaged communities, aligning with the goals of Sharia economics. Community involvement is integral to this process. This research aims to provide a general overview of the importance of community involvement in the empowerment process. This research is a literature study whose data source comes from articles with the keyword